2004
DOI: 10.1182/blood-2003-08-2981
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular serpin SERPINB6 (PI6) is abundantly expressed by human mast cells and forms complexes with β-tryptase monomers

Abstract: SERPINB6 (PI6) is a member of the intracellular serine protease inhibitors (serpins). Previous studies showed that SERPINB6 is localized mainly in the cytoplasm of endothelial cells, some epithelial cells, monocytes, and neutrophils. In these cells SERPINB6 is thought to prevent cellular damage by scavenging leaking lysosomal proteases. We show here, using novel, well-defined monoclonal antibodies, that SERPINB6 is abundantly expressed by mast cells in all organs and by the human mast cell line HMC-1. Gel filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…We observed leptin expression in the MCs within the lesion. In all tumour MCs, the staining for both MC markers was less pronounced compared to the expression level of MCs in the normal skin, which is in congruence with previous literature (Strik et al 2004). Leptin receptor expression was studied in Wve patients with skin mastocytosis to evaluate if leptin receptors are also present on neoplastic MCs.…”
Section: Discussionsupporting
confidence: 63%
“…We observed leptin expression in the MCs within the lesion. In all tumour MCs, the staining for both MC markers was less pronounced compared to the expression level of MCs in the normal skin, which is in congruence with previous literature (Strik et al 2004). Leptin receptor expression was studied in Wve patients with skin mastocytosis to evaluate if leptin receptors are also present on neoplastic MCs.…”
Section: Discussionsupporting
confidence: 63%
“…SERPINB6 is also known as proteinase inhibitor 6 or placental thrombin inhibitor, and may contribute to the secondary pathology of myelomeningocele for its role in anti-viral, anti-apoptotic effects, and fibrinolysis. 3436 SERPINB6 also endogeneously inhibits neuropsin, which modifies synaptic plasticity and long-term potentiation. 37,38 Many other genes with previously unknown associations with myelomeningocele or spinal development were up- or down-regulated, but none to the extent of SERPINB6 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that monomers formed under certain conditions have some distinct enzymatic activity [23][24][25] and appear to be responsible for the cleavage of some large proteins [23], but in contrast to the tetramer are sensitive to endogenous inhibitors, e.g. antithrombin III, serpin B6, and -2-macroglobulin [24,26].…”
Section: Tryptasementioning
confidence: 98%